Teknik Art Therapy “Membatik” Untuk Meningkatkan Kecerdasan Emosional Peserta Didik Sekolah Menengah Pertama - Rahmiawan, Natasya Artamefilla; Khusumadewi, Ari; Purwoko, Budi; Winingsih, Evi (Fakultas Tarbiyah dan Keguruan, 2024)
Adolescence is characterized by emotional instability, which often leads to low emotional intelligence in individuals. This study aims to evaluate the effectiveness of art therapy techniques in improving adolescents' emotional intelligence. Using the Systematic Literature Review (SLR) method, journal searches were conducted online with the keywords